Identification of Medicinal Bidens Plants for Quality Control Based on Organelle Genomes - Wu, Liwei; Nie, Liping; Guo, Shiying; Wang, Qing; Wu, Zhengjun; Lin, Yulin; Wang, Yu; Li, Baoli; Gao, Ting; Yao, Hui (Frontiers in Pharmacology, 2022)
Bidens plants are annuals or perennials of Asteraceae and usually used as medicinal materials in China. They are difficult to identify by using traditional identification methods because they have similar morphologies and chemical components. Universal DNA barcodes also cannot identify Bidens species effectively. This situation seriously hinders the development of medicinal Bidens plants. Therefore, developing an accurate and effective method for identifying medicinal Bidens plants is urgently needed. The present study aims to use phylogenomic approaches based on organelle genomes to address the confusing relationships of medicinal Bidens plants. Illumina sequencing was used to sequence 12 chloroplast and eight mitochondrial genomes of five species and one variety of Bidens. The complete organelle genomes were assembled, annotated and analysed. Phylogenetic trees were constructed on the basis of the organelle genomes and highly variable regions. The organelle genomes of these Bidens species had a conserved gene content and codon usage. The 12 chloroplast genomes of the Bidens species were 150,489 bp to 151,635 bp in length. The lengths of the eight mitochondrial genomes varied from each other. Bioinformatics analysis revealed the presence of 50–71 simple sequence repeats and 46–181 long repeats in the organelle genomes. By combining the results of mVISTA and nucleotide diversity analyses, seven candidate highly variable regions in the chloroplast genomes were screened for species identification and relationship studies. Comparison with the complete mitochondrial genomes and common protein-coding genes shared by each organelle genome revealed that the complete chloroplast genomes had the highest discriminatory power for Bidens species and thus could be used as a super barcode to authenticate Bidens species accurately. In addition, the screened highly variable region trnS-GGA-rps4 could be also used as a potential specific barcode to identify Bidens species.